2001
DOI: 10.1037/0021-9010.86.2.316
|View full text |Cite
|
Sign up to set email alerts
|

The role of justice in team member satisfaction with the leader and attachment to the team.

Abstract: This study examined the effects of team decision accuracy, team member decision influence, leader consideration behaviors, and justice perceptions on staff members' satisfaction with the leader and attachment to the team in hierarchical decision-making teams. The authors proposed that staff members' justice perceptions would mediate the relationship between (a) team decision accuracy, (b) the amount of influence a staff member has in the team leader's decision, and (c) the leader's consideration behaviors and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
52
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(57 citation statements)
references
References 43 publications
2
52
0
Order By: Relevance
“…For example, supervisory PJ has been found to promote effort on behalf of and attachment with the group (Philips, Douthitt, & Hyland, 2001). Elsewhere, Korsgaard et al (2002) found that managers' trustworthy behavior, as measured by communication and concern shown toward subordinates, was positively related with coworker helping behavior.…”
Section: Supervisory Pj and Helping Behavior: Mediated By Affective Tmentioning
confidence: 97%
“…For example, supervisory PJ has been found to promote effort on behalf of and attachment with the group (Philips, Douthitt, & Hyland, 2001). Elsewhere, Korsgaard et al (2002) found that managers' trustworthy behavior, as measured by communication and concern shown toward subordinates, was positively related with coworker helping behavior.…”
Section: Supervisory Pj and Helping Behavior: Mediated By Affective Tmentioning
confidence: 97%
“…members of self-managing teams (Kirkman et al, 1996;Shapiro and Kirkman, 1999), hierarchical decision-making teams (Phillips et al, 2001), and strategic decision-making teams (Korsgaard et al, 1995). Similar to the tenets of equity theory (Adams, 1965), which argues that people form perceptions of justice by comparing their own outcomes and inputs to those of comparison others, the findings of research on justice in teams suggest that individuals determine the extent to which differential treatment within groups is legitimate and make judgments about how procedures and outcomes experienced by other team members affect them (Colquitt et al, 2005).…”
mentioning
confidence: 99%
“…In addition to sharing knowledge, leaders and their peers must mutually support each other in order to build team relations. A reciprocal relationship of trust, enthusiasm, justice, and praise improves team member satisfaction and productivity (Phillips et al, 2001;Chen et al, 2008). Leaders that initiate change and support their team members establish a creative and more satisfying work climate (Sellgren et al, 2008).…”
Section: Peer Teaching and Leadership In The Human Structure Blockmentioning
confidence: 98%